When Special Education and Disability Studies Intertwine: Addressing Educational Inequities Through Processes and Programming - Sandoval Gomez, Audri; McKee, Aja (Frontiers in Education, 2020)
The inception of the Education for All Handicapped Children Act (EAHCA) in 1975 provided hope and the opportunity for equitable educational experiences for individuals with disabilities. Forty-five years later, the United States remains in a deficit-driven, medical model educational system with deeply rooted inequities continuing to segregate students because of their disability. A disability studies in education framework allows for complex components of teaching and programming for students with disabilities to be explored in a practical way that promotes inclusive education for all students. Examining special education practices through a social model of disability with a focus on ability and access can eliminate the existing narrative. When impairment is viewed as a difference rather than a deficit, it compels educators to consider alternatives to pedagogy and programming. More importantly, it allows educators to focus more on access to curricula and less on students overcoming their disability. This manuscript examines how educational leaders can shape school culture, guide special education processes, and influence educators in their teaching practices, with a disability studies in education framework to address the educational injustices students with disabilities continue to face in our educational system.